2022
DOI: 10.1177/15330338221112280
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Optical Surface Respiratory Motion Signal and Internal Lung and Liver Tumor Motion: A Retrospective Single-Center Observational Study

Abstract: Purpose: Surface-guided radiation therapy (SGRT) application has limitations. This study aimed to explore the relationship between patient characteristics and their external/internal correlation to qualitatively assess the external/internal correlation in a particular patient. Methods: Liver and lung cancer patients treated with radiotherapy in our institution were retrospectively analyzed. The external/internal correlation were calculated with Spearman correlation coefficient (SCC) and SCC after support vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…In addition, the targets in our study were the magnitudes of respiratory motion, rather than internal targets that were treated by a medical linear accelerators or surgical robots. However, several studies (Lee et al 2018, Park et al 2018, Wang et al 2022 have demonstrated the strength and stability of the correlation between internal targets and respiratory motion, which means that EEG neural signals-based respiratory motion tracking is a potential solution to respiratory motion of internal targets in radiotherapy and robotic surgery. More importantly, a simplified 256-channel EEG might be able to capture respiratory-related neural signals owing to that the 256-channel EEG was initially designed to capture various brain activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the targets in our study were the magnitudes of respiratory motion, rather than internal targets that were treated by a medical linear accelerators or surgical robots. However, several studies (Lee et al 2018, Park et al 2018, Wang et al 2022 have demonstrated the strength and stability of the correlation between internal targets and respiratory motion, which means that EEG neural signals-based respiratory motion tracking is a potential solution to respiratory motion of internal targets in radiotherapy and robotic surgery. More importantly, a simplified 256-channel EEG might be able to capture respiratory-related neural signals owing to that the 256-channel EEG was initially designed to capture various brain activities.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the ROI selection, Jiateng Wang et al noted that the correlation between tumor and skin motion can vary greatly between tumors and patients, implying that, when planning lung and liver SBRT motion management, individual patient and tumor characteristics should always be considered [28].…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 The external/internal correlation between external and internal respiratory motion has nothing to do with tumor clinical characteristics such as tumor location, pulmonary function, and size, as well as patient breathing pattern, and other information. 20 , 22 Other findings suggest that external respiratory motion waveforms do not always accurately correspond to the tumor motion in lung cancer patients, 23 and an external surrogate may not be sufficient to predict complex tumor motion. 24 , 25 This may lead to the target location being missing when an external surrogate is used to guide treatment in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“… 27 In our previous study, the correlation was calculated considering the Spearman correlation coefficient (SCC) and SCC after support vector regression fitting. 22 However, these methods all require significant additional data acquisition and processing. In the study, we report a novel approach to predict the correlation based on CT radiomic features through machine learning.…”
Section: Introductionmentioning
confidence: 99%